A task offloading optimization strategy in MEC‐based smart cities. Issue 1 (20th April 2020) - Li, Shuangyuan
Abstract : The Mobile Edge Computing (MEC) technology can greatly facilitate the development of smart cities, as a result, MEC‐based smart cities have attracted much attention from some global research communities. In such filed, there is always a non‐negligible challenge, that is, efficient task offloading from mobile devices to edge servers. To this end, this letter proposes a task offloading optimization strategy to make a tradeoff between energy consumption and response time, including the modeling of two sub‐objectives and a heuristic bi‐objective optimization algorithm. The proposed strategy is simulated and the experimental results demonstrate that it is more efficient compared to the the‐state‐of‐the‐art strategy.